2020
DOI: 10.1001/jamacardio.2020.1855
|View full text |Cite
|
Sign up to set email alerts
|

Association of Use of Angiotensin-Converting Enzyme Inhibitors and Angiotensin II Receptor Blockers With Testing Positive for Coronavirus Disease 2019 (COVID-19)

Abstract: IMPORTANCEThe role of angiotensin-converting enzyme inhibitors (ACEI) and angiotensin II receptor blockers (ARB) in the setting of the coronavirus disease 2019 (COVID-19) pandemic is hotly debated. There have been recommendations to discontinue these medications, which are essential in the treatment of several chronic disease conditions, while, in the absence of clinical evidence, professional societies have advocated their continued use. OBJECTIVE To study the association between use of ACEIs/ARBs with the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
476
6
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 385 publications
(516 citation statements)
references
References 21 publications
20
476
6
14
Order By: Relevance
“…In total, 10 studies comprising of 49,188 patients were included in this analysis. Of these, 4,274 SARS-CoV-2 positive patients were taking ACEIs/ARBs whereas 8,714 positive patients were non users of ACEIs/ARBs 1,[19][20][21][22][23][24][25][26][27] . Of these, eight studies provided data on mortality outcome, seven studies provided data on composite severe clinical manifestations outcome and only two studies provided data on SARS-CoV-2 test positivity as shown in Table 1.…”
Section: General Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 10 studies comprising of 49,188 patients were included in this analysis. Of these, 4,274 SARS-CoV-2 positive patients were taking ACEIs/ARBs whereas 8,714 positive patients were non users of ACEIs/ARBs 1,[19][20][21][22][23][24][25][26][27] . Of these, eight studies provided data on mortality outcome, seven studies provided data on composite severe clinical manifestations outcome and only two studies provided data on SARS-CoV-2 test positivity as shown in Table 1.…”
Section: General Characteristics and Quality Of Included Studiesmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is leading to huge morbidity and mortality throughout the world since it was rst detected in early December of 2019 in Wuhan, China 1 . It has already been established that the SARS-CoV-2 binds to the angiotensin-converting enzyme 2 (ACE2) receptor of extracellular domain of the transmembrane to gain entry into the host cells 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations